Intelligent soccer training. Simulating games to improve technique & tactics - Fincke, A.; Seeger, F. (Meyer & Meyer Sport (UK) Ltd., 2020)
Intelligent Soccer Training is the follow-up book to The Soccer Games and Drills Compendium: 350 Smart and Practical Games to Form Intelligent Players - For All Levels. The 150 training forms teach the basic tactical and technical skills of modern soccer. The book discusses running behavior (running, chasing, and catching), techniques (ball control, dribbling, first-touch control, passing, and shooting), group tactics, variable games entries, as well as the improvement of action speed and game intelligence. With its wide range of information, the content presented addresses all playing ages and performance levels. Intelligent Soccer Training qualitatively differs from known training content to present innovative and modern training forms of basic training, developing new forms and thus extending the range of exercise and play for the interested coach. Ultimately, the trainer should get to know new exercises and modern and additional forms of play to expand his repertoire accordingly to be able to offer a varied and motivating training for his players. Following the practice-oriented section is the theory of intelligent training, which further answers questions about training and competition. In this section, aspects such as talent definition, talent development, management composition, teaching and learning techniques, game system, position specifics, and training atmosphere are covered, so that all players and coaches will have the knowledge and skills needed to excel at the game of soccer. Verlagsinfo From content: